Methimazole‐induced cholestasis initially obscured by an incidental finding of a large periampullary diverticulum: A case report with reference to the updated RUCAM of 2016 - Salomon Chamay; Ari Alter; Rooshi Parikh; Shivam Khatri; Deepa Budh; Mitchell Spinnell (JGH Open)
Abstract Methimazole is a commonly prescribed drug for hyperthyroidism and is generally well‐tolerated, with complications occurring in less than 10% of treated patients. To our knowledge, there are approximately 30 reported cases of drug‐induced liver injury (DILI) associated with the use of methimazole in the literature. DILI is a challenging diagnosis and can often mimic many forms of acute and chronic hepatitis. The pattern of liver injury can be hepatocellular, cholestatic, or mixed in nature. The R‐value is a useful tool for characterizing the pattern of liver injury, while the Roussel Uclaf Causality Assessment Method (RUCAM) aids with quantifying the likelihood of DILI. The updated version of RUCAM from 2016 was used in this report. We present a case of a 72‐year‐old female who developed cholestatic DILI secondary to methimazole with a calculated RUCAM score of 8, initially obscured by both imaging and endoscopic findings concerning for hepatobiliary obstruction.